Bacterial DNA methyltransferase: A key to the epigenetic world with lessons learned from proteobacteria - Gao, Qun; Lu, Shuwei; Wang, Yuwei; He, Longgui; Wang, Mingshu; Jia, Renyong; Chen, Shun; Zhu, Dekang; Liu, Mafeng; Zhao, Xinxin; Yang, Qiao; Wu, Ying; et al. (Frontiers in Microbiology, 2023)
Epigenetics modulates expression levels of various important genes in both prokaryotes and eukaryotes. These epigenetic traits are heritable without any change in genetic DNA sequences. DNA methylation is a universal mechanism of epigenetic regulation in all kingdoms of life. In bacteria, DNA methylation is the main form of epigenetic regulation and plays important roles in affecting clinically relevant phenotypes, such as virulence, host colonization, sporulation, biofilm formation et al. In this review, we survey bacterial epigenomic studies and focus on the recent developments in the structure, function, and mechanism of several highly conserved bacterial DNA methylases. These methyltransferases are relatively common in bacteria and participate in the regulation of gene expression and chromosomal DNA replication and repair control. Recent advances in sequencing techniques capable of detecting methylation signals have enabled the characterization of genome-wide epigenetic regulation. With their involvement in critical cellular processes, these highly conserved DNA methyltransferases may emerge as promising targets for developing novel epigenetic inhibitors for biomedical applications.